Metacognition and Goal-Orientations. Their Role in Self-Regulation of Learning in Physical Education - Theodosiou Αργύρης; Papaioannou Αθανάσιος (Inquiries in Physical Education and Sport, 2006)
In the following article an attempt is made to be comprehended by the reader what metacognition is and its’ importance for the production of new knowledge in general, and particularly in Physical Education settings. Metacognitive activities are important for the production of new knowledge because they help people to monitor and to regulate their own learning. People’s goal-orientations play particular role for the more frequent use of metacognitive strategies as such, according the goal-perspective theory, they affect the way they approach learning and the percentage of their participation in it. The character of the learning environment engenders the appropriate background for greater cognitive self-regulation whether indirectly, by affecting the modulation of goal-orientations, or directly offering more chances for the application of metacognitive strategies. The aim of Physical Educators should be the development of a motivation climate that promotes personal improvement because apart from the positive influences on students’ intrinsic motivation, also advances the more frequent use of metacognitive strategies during learning process.